Cerebrospinal Fluid Features in Patients With Coronavirus Disease 2019 and Neurological Manifestations: Correlation with Brain Magnetic Resonance Imaging Findings in 58 Patients. (29th November 2020) - Lersy, François; Benotmane, Ilies; Helms, Julie; Collange, Olivier; Schenck, Maleka; Brisset, Jean-Christophe; Chammas, Agathe; Willaume, Thibault; Lefebvre, Nicolas; Solis, Morgane; Hansmann, Yves; Fabacher, Thibaut; et al.
Abstract: Background: Neurological manifestations are common in patients with coronavirus disease 2019 (COVID-19), but little is known about pathophysiological mechanisms. In this single-center study, we examined neurological manifestations in 58 patients, including cerebrospinal fluid (CSF) analysis and neuroimaging findings. Methods: The study included 58 patients with COVID-19 and neurological manifestations in whom severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) reverse-transcription polymerase chain reaction screening and on CSF analysis were performed. Clinical, laboratory, and brain magnetic resonance (MR) imaging data were retrospectively collected and analyzed. Results: Patients were mostly men (66%), with a median age of 62 years. Encephalopathy was frequent (81%), followed by pyramidal dysfunction (16%), seizures (10%), and headaches (5%). CSF protein and albumin levels were increased in 38% and 23%, respectively. A total of 40% of patients displayed an elevated albumin quotient, suggesting impaired blood-brain barrier integrity. CSF-specific immunoglobulin G oligoclonal band was found in 5 patients (11%), suggesting an intrathecal synthesis of immunoglobulin G, and 26 patients (55%) presented identical oligoclonal bands in serum and CSF. Four patients (7%) had a positive CSF SARS-CoV-2 reverse-transcription polymerase chain reaction. Leptomeningeal enhancement was present on brain MR images in 20 patients (38%). Conclusions: Brain MR imaging abnormalities, especially leptomeningeal enhancement, and increased inflammatory markers in CSF are frequent in patients with neurological manifestations related to COVID-19, whereas SARS-CoV-2 detection in CSF remained scanty. Abstract : Cerebrospinal fluid abnormalities were frequent in patients with neurological manifestations related to coronavirus disease 2019, whereas severe acute respiratory syndrome coronavirus 2 detection in cerebrospinal fluid remained scanty.